Identity in Family Firms: A Theoretical Analysis of Incentives and Contracts - Marcelo Sanches Pagliarussi; Cristiano Costa (BAR: Brazilian Administration Review, 2017)
We developed a principal-agent model that coherently and parsimoniously explains previous findings from research on executive compensation in family firms. We introduce organizational identification in the model in order to capture the effect of family firms’ distinctive characteristics on the agent’s behavior. After describing the optimal incentive contract under moral hazard, we show that the dispersion in the optimal wage profile decreases as the level of organizational identification of the agent increases. Moreover, we show that agency costs decrease as the level of organizational identification of the agent increases. Our results imply that hiring a strongly identified family manager will result in greater expected wealth to the principal and better risk sharing between the parties. We further analyze two interrelated factors that may drive changes in contract parameters: the degree of altruism in the family firm, and the level of collectivism of the society in which the firm is located.